Improving student activities and learning outcomes through implementation of pop-up book media in discovery learning - Yulia, Yulia; Kurniati, Kurniati; Krismanto, Wawan (Electronic Journal of Education, Social Economics and Technology, 2022)
One of the crucial things in achieving maximum learning outcomes is using learning media that can facilitate active student learning. Therefore this study aims to examine the use of Pop-up book media in discovery learning to improve student learning processes and outcomes. The approach is qualitative, with a classroom action research type. The research subjects were 12 grade IV students at SDN 105 Pinrang. This research was conducted in 2 cycles. Observation techniques, tests, and documentation obtained data. This study focuses on the learning process (student activities) and student learning outcomes. The results showed that the learning process (student activities) using Pop-up book media in discovery learning in cycles I and II improved. In line with the improvement in the learning process, student learning outcomes also increased from having sufficient qualifications in cycle I to be well qualified in cycle II. This study concludes that using pop-up book media in discovery learning can improve the process (student activities). The learning process becomes more lively because two-way communication is established, students active participation makes learning more meaningful and powerful. The learning syntax in discovery learning can facilitate students using pop-up book media because it can stimulate students to be active in learning. Students are encouraged to identify material in the media, and the use of pop-up book media in learning discovery learning changes teacher-oriented learning to student-oriented. This positively impacts student learning outcomes, which increase as the learning process increases.